ANALYSIS OF TERRITORIAL DEVELOPMENT OF THE REPUBLIC OF BURYATIA - Olga A. Popova (Статистика и экономика)
The article describes some aspects of the analysis of territorial development of the region. The focus is on the planned and actual indicators of territorial development of the region. Analysis of the three major indicators of territorial development: the volume of capital investment, tax and non-tax revenues of the consolidated budget, production of industrial and agricultural products. When assessing the proposed region development to assess not only the actual execution of the planned indicators, but in order to assess the effectiveness of regional development planning system to compare planned and actual growth of indicators.